How the analytical hierarchical process and revitalisation work together: A case study of Poland - Rogatka, Krzysztof; Starczewski, Tomasz; Kowalski, Mateusz (Quaestiones Geographicae, 2022)
Due to the multifaceted nature of the revitalisation process, its evaluation and monitoring, as well as possible comparisons, are complex and difficult to carry out. Evaluation of the revitalisation process currently poses a challenge for all municipalities. The article aims to compare the revitalisation process in the two Polish cities of Toruń and Bydgoszcz. The analysis was based on two financial perspectives: 2007–2015 and 2016–2023. The authors chose a multi-criteria analysis method based on the analytical hierarchical process (AHP) as the main research method. The results show that the Local Revitalisation Programme of the City of Toruń for the years 2007–2015 had the best impact on the revitalisation process. Using the AHP method, we could carry out a multidimensional evaluation of the revitalisation process. Moreover, it allowed us to combine different elements of the evaluation of the revitalisation process and transform them into one synthetic result, ranking each programme in a hierarchy. At the methodological level, the article presents a new approach to conduct research in socio-economic geography, using the tool of multi-criteria analysis derived from the disciplines of economics and management sciences. Until now, the AHP method has not been used in the analysis of the revitalisation process, which confirms the innovative character of the conducted research.